1998
DOI: 10.1073/pnas.95.26.15542
|View full text |Cite
|
Sign up to set email alerts
|

Anti-β2 glycoprotein I (β2GPI) autoantibodies recognize an epitope on the first domain of β2GPI

Abstract: Anticardiolipin (aCL) autoantibodies are associated with thrombosis, recurrent fetal loss, and thrombocytopenia. Only aCL found in autoimmune disease require the participation of the phospholipid binding plasma protein ␤2 glycoprotein I (␤2GPI) for antibody binding and now are called anti-␤2GPI. The antigenic specificity of aCL affinity purified from 11 patients with high titers was evaluated in an effort to better understand the pathophysiology associated with aCL. Seven different recombinant domain-deleted m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
213
1
7

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(229 citation statements)
references
References 35 publications
8
213
1
7
Order By: Relevance
“…If domain IV does contain the major epitope for aPL, then the DMs for domains II-V, III-V, and IV-V would be expected to bind aPL to variable degrees. These mutants were either not examined (80,81) or found to be unable to bind aPL (57). Thus, the data from Iverson et al complements and extends the findings from the other two groups, and clearly implicates domain I in the binding of aPL, particularly since they found that the domains I-II and domain I DMs both bound aPL (57).…”
Section: Which Domains Of ␤ 2 Gpi Contain Major Epitopes For Apl?supporting
confidence: 55%
See 1 more Smart Citation
“…If domain IV does contain the major epitope for aPL, then the DMs for domains II-V, III-V, and IV-V would be expected to bind aPL to variable degrees. These mutants were either not examined (80,81) or found to be unable to bind aPL (57). Thus, the data from Iverson et al complements and extends the findings from the other two groups, and clearly implicates domain I in the binding of aPL, particularly since they found that the domains I-II and domain I DMs both bound aPL (57).…”
Section: Which Domains Of ␤ 2 Gpi Contain Major Epitopes For Apl?supporting
confidence: 55%
“…Iverson et al (57) studied the reactivity of aPL with various ␤ 2 GPI domain-deleted mutants (DM) expressed in insect cells. The expression vectors were designed such that expression products contained carboxyl-terminal Gly/His-6 tags for binding to nickel chelate plates.…”
Section: Molecular Structure and Function Of ␤ 2 Gpimentioning
confidence: 99%
“…β2GP1 is composed of five "sushi" domains. Domain V mediates the binding of the molecule to anionic phospholipids while domain I seems to be the main target of antibodies associated with an increased risk of thrombosis [24,25]. At least two different conformations are known for β2GP1: a circular plasma conformation in which domain I interacts with domain V and an "activated" fishhook-like conformation [26].…”
Section: Cell Activation By Aplamentioning
confidence: 99%
“…The bulk of the evidence favors aPL binding immunodominant epitopes located within the N-terminal (domain I) (13)(14)(15). The ability of anti-␤ 2 GPI antibodies purified from patients with autoimmune disease to bind domain I of ␤ 2 GPI has been shown to be strongly correlated with the occurrence of thrombosis in those patients (16).…”
mentioning
confidence: 99%